Awareness of Paddy Residue Utilization in Karnal and Kurukshetra Districts of Haryana State (Indian Journal of Extension Education, 2022)
Study was conducted in 2021-22 to assess the awareness level of farmers regarding utilization of paddy residue in Karnal and Kurukshetra districts of Haryana state. A well structured and pre-tested interview schedule was developed according to the objective of the study. Two blocks were selected randomly from each district. Further, one village from each block was also selected randomly. So, four villages were selected to collect data. Further, from each selected village, 75 male paddy growing farmers having more than 5 acres of land were selected through snowball technique. Thus, total 300 respondents were interviewed. Present study concluded that all respondents (100.00%) were aware about straw baler machine and feeding the livestock, followed by making cattle shed roof (96.33%), hey rake (93.67) and mulching in the field (93.67). Study also concluded that sufficient time to sow next crop because it takes one and half months to decompose, paddy straw management delays wheat sowing and paddy residue burning is cheap option were major reasons for paddy residue burning.